2007
DOI: 10.1038/nn1960
|View full text |Cite
|
Sign up to set email alerts
|

OL-protocadherin is essential for growth of striatal axons and thalamocortical projections

Abstract: The ventral telencephalon in the embryonic brain is thought to provide guidance cues for navigation of thalamocortical axons, but the mechanisms involved remain largely elusive. OL-protocadherin (OL-pc), a member of the cadherin superfamily, is highly expressed by striatal neurons in the developing ventral telencephalon. Here we show that OL-pc-deficient (Pcdh10(-/-)) mice have defects in axon pathways through the ventral telencephalon; for example, thalamocortical and corticothalamic projections cannot cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
157
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 41 publications
12
157
5
Order By: Relevance
“…19,20 In addition, in Pax6 and Emx2 knock-out mice, both Nkx2.1 cells and TC axons follow abnormal striatal axon pathways. 9 On the other hand, our observation is not consistent with the "hand-shake" hypothesis; 2,3 i.e., in the OL-protocadherin KO mice, CT axons proceeded into the VT to the striatum/GP region in the absence of TC axons, suggesting TC axons are not required for guidance of CT axons at least to this region. Although we could not prove this hypothesis experimentally, our results suggest the importance of striatal axons in the early events of TC guidance in the VT. Figure 2.…”
contrasting
confidence: 75%
See 2 more Smart Citations
“…19,20 In addition, in Pax6 and Emx2 knock-out mice, both Nkx2.1 cells and TC axons follow abnormal striatal axon pathways. 9 On the other hand, our observation is not consistent with the "hand-shake" hypothesis; 2,3 i.e., in the OL-protocadherin KO mice, CT axons proceeded into the VT to the striatum/GP region in the absence of TC axons, suggesting TC axons are not required for guidance of CT axons at least to this region. Although we could not prove this hypothesis experimentally, our results suggest the importance of striatal axons in the early events of TC guidance in the VT. Figure 2.…”
contrasting
confidence: 75%
“…Our recent paper on the analysis of OL-protocadherin-deficient mice has cast some light and provided novel insight into this issue. 9 Protocadherins are, by definition, cell-adhesion molecules with 6 or 7 cadherin motifs in their extracellular domain and various cyotoplasmic domains. 10 The family in the mammalian genome consists of about 50 members; and protocadherin a (CNR) genes, protocadherin b (protocadherin 3) genes, and protocadherin g (protocadherin 2) genes constitute gene clusters on a single chromosome; 11 whereas others are scattered over different chromosomes (see review by Hirano et al 2003, ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, forced expression of Pcdh17 in a group of axons that did not originally express this protocadherin changes their extension path and leads them to intermingle with axons that endogenously express the same d2-protocadherin (Hayashi et al, 2014), supporting the idea that d2-protocadherins might be involved in axon sorting. By contrast, despite the broad expression of d2-protocadherins in the brain, abnormalities in brain morphogenesis have been detected in only restricted regions of the brains of d2-protocadherinknockout mice (Hayashi et al, 2014;Uemura et al, 2007). Although the failure to detect phenotypes in knockout mice can be explained by assuming the functional redundancy of the genes or proteins that have been analyzed, it is equally possible that conventional histology does not detect subtle deficiencies occurring in a small population of neuronal cells.…”
Section: Potential Mechanisms Of D2-protocadherin-mediated Axon Extenmentioning
confidence: 99%
“…Pcdh10 (also known as OLprotocadherin) and Pcdh17 are detected along axon fibers (Hayashi et al, 2014;Uemura et al, 2007), suggesting that they are involved in axon development or function. It has, indeed, been reported that gene knockout of Pcdh10 in mice causes defects in the formation of various axon tracts, such as the thalamocortical and corticospinal tracts that connect the cerebral cortex and other regions of the central nervous system (Uemura et al, 2007). However, analysis of another Pcdh10-knockout mouse line, which was generated independently of that used in the study described previously, failed to detect such phenotypes (I. Kahr, F. van Roy and S. Hirano, personal communication).…”
Section: Role Of D2-protocadherins In Axon Growth and Patterningmentioning
confidence: 99%